Acceptance Sampling Plans Based on Truncated Life Tests for Sushila Distribution - Amer Ibrahim Al-Omari (Journal of Mathematical and Fundamental Sciences, 2018)
An acceptance sampling plan problem based on truncated life tests when the lifetime following a Sushila distribution is considered in this paper. For various acceptance numbers, confidence levels and values of the ratio between fixed experiment time and particular mean lifetime, the minimum sample sizes required to ascertain a specified mean life were found. The operating characteristic function values of the suggested sampling plans and the producer's risk are presented. Some tables are provided and the results are illustrated by an example of a real data set.